VACLOVAS BIRŽIŠKA’S CONCEPTION OF SAMOGITIAN BOOK - PETREIKIS, TOMAS (Knygotyra, 2010)
The influence of regional identity on Prof. Vaclovas Biržiška’s scholarly activities is analyzed in the article. The origin, genesis and realization of the Samogitian book conception are revealed in more detail. V. Biržiška’s regional identity, which rested upon Samogitians’ (sub)ethical consciousness, encouraged him to accentuate the Samogitian book in the book history of Great Lithuania. These tendencies were sporadically reflected in V. Biržiška’s bibliographical activities which were summarized in his “Lithuanian Bibliography”. V. Biržiška’s source-researching works and publications on the written heritage also show his particular attention to the heritage of Samogitian books. These tendencies remained quite vivid in V. Biržiška’s bibliographical works, therefore the characteristics of Samogitian writing attained more particular researches, among which the study about bishop Motiejus Valančius was brought to the fore. The interest in the history of Samogitian book induced Professor to formulate the conception of Samogitian book, which referred to the ethnic book model. The conception was stated in the article “The Samogitian book” (1927) in the form of a bibliographical review. In V. Biržiška’s conception, the Samogitian book is one of the integral courses of regional book researches. After being published, this new course of research was not amplified and the conception was not realized. Even though the scholar did not abandon the further analysis of the sporadic questions of the Samogitian book history, the conception of regional research is absent in the later works of V. Biržiška. Lithuanians’ lack of maturity in book science encouraged V. Biržiška to pursue the unified and generalizing researches of Great Lithuania’s book history, whereas there were no appropriate circumstances and no potential for dividing them into separate regional groups.